2021
DOI: 10.24221/jeap.6.4.2021.3616.352-362
|View full text |Cite
|
Sign up to set email alerts
|

A sucessão florestal e a arquitetura vegetal influenciam a herbivoria em Cenostigma pyramidale em Floresta Tropical Sazonal Seca?

Abstract: A herbivoria pode ser influenciada pelas características defensivas vegetais e pelo terceiro nível trófico bem como pela arquitetura da planta. A Caatinga possui áreas com diferentes idades de regeneração natural após abandono. O objetivo foi avaliar se o estádio sucessional de regeneração e arquitetura vegetal influenciam a herbivoria. Cenostigma pyramidale foi usada como planta modelo por ocorrer nos três estádios sucessionais (inicial, intermediário e tardio). Foram amostrados insetos herbívoros e aranhas a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…Oliveira and Almeida [89] demonstrated that leaves of C. pyramidale, which developed in the dry season, were more tender and sclerophyllous than leaves collected in the rainy season. In this study, we describe that in the rainy year, the less rainfall caused an increase in TLT, ADAE, ABAE, and PP, respectively in 24.9%, 19.7%, 27.9%, and 70.8% aligned with Taratima et al [90] and Taratima et al [91] which described that anatomical adaptations also do occur under drought stress with an increase in the cuticle, epidermis, and leaf thickness prevent water loss.…”
Section: Discussionmentioning
confidence: 99%
“…Oliveira and Almeida [89] demonstrated that leaves of C. pyramidale, which developed in the dry season, were more tender and sclerophyllous than leaves collected in the rainy season. In this study, we describe that in the rainy year, the less rainfall caused an increase in TLT, ADAE, ABAE, and PP, respectively in 24.9%, 19.7%, 27.9%, and 70.8% aligned with Taratima et al [90] and Taratima et al [91] which described that anatomical adaptations also do occur under drought stress with an increase in the cuticle, epidermis, and leaf thickness prevent water loss.…”
Section: Discussionmentioning
confidence: 99%